Korean Wave and NCT Dream Brand Ambassador and its Influence on Interest in Buying Products on Twitter Followers @lemonilo - Putri, Elvina Maharani; Harmadi, Ashur; Ohorella, Noviawan Rasyid; Sari, Diana (Technium Social Sciences Journal, 2023)
This study aims to analyze the influence of the Korean wave and the NCT Dream brand ambassador from the South Korean boy group on buying interest in Mie Lemonilo products. Intense competition makes a brand must be selective in promoting its products in order to compete in a healthy manner. Therefore, trending marketing activities are carried out by companies in this digital era, namely taking advantage of the current Korean wave trend and the popularity of celebrities by using brand ambassadors. This study uses the A-T-R theory (Awareness-Trial & Reinforcement) with the analytical tool used is the quantitative method by distributing questionnaires. The data used in this research is primary data using a questionnaire with a sample of 100 people from followers of the official Twitter account @lemonilo, totaling 33,120 followers (7 April 2022). The results of the study partially show that the coefficient value of the Korean wave variable (X1) has a positive value of 0.606 and the NCT Dream variable as a brand ambassador (X2) has a positive value of 0.324 on interest in buying Lemonilo Noodles (Y). Simultaneously, there is an influence between the independent variables Korean Wave and Brand Ambassador on the dependent variable Purchase Interest of 47.4%, which means that there is the influence of Korean Wave and NCT Dream as Brand Ambassadors on Purchase Interest for Lemonilo Noodle products.